Interannual Variations of D14CTOC and Elemental Contents in the Laminated Sediments of the Santa Barbara Basin During the Past 200 Years - Li, Hong-Chun; Chang, Yiwei; Berelson, William M.; Zhao, Meixun; Misra, Satabdi; Shen, Tzu-Tsen (Frontiers in Marine Science, 2022)
A 51-cm core (SBB-8-2012) from the depo-center of Santa Barbara Basin (SBB), California has been dated by 210Pb dating and varve counting, spanning a depositional history during 1815-2011 CE. A total of 89 AMS 14C measurements on samples from 66 horizons, including animal cartilage, shell and total organic carbon (TOC) in the sediments show apparent 14C ages between 500 and 4000 yr BP. Among these AMS dates, D14C values measured in 78 samples from 62 horizons vary in the range of -64.3‰ to -383.8‰. The 14CTOC ages much older than predicted from our sedimentation model are influenced by the input of terrigenous sediments, changes in ocean circulation, biological input and carbon remineralization. Three strong old 14CTOC excursions at 1964 69, 1884 87 and 1819 21 CE indicate higher old carbon input caused by some unusual events (e.g., oil spill, flood event and earthquake). On multi-decadal timescales, the D14CTOC shifts in three zones were mainly caused by changes in fossil carbon emission from the seafloor, fraction of marine productivity to terrigenous input of organic carbon (OC) and the atmospheric nuclear bomb testing input of 14C into the SBB. On interannual to decadal timescales, variations of D14CTOC correspond to El Niño-Southern Oscillation effects. During the La Niña period, stronger upwelling and northerly California Current bring nutrient-enriched water into SBB and lead to higher productivity hence more marine OC with higher D14CTOC. In addition, reduced terrigenous input of OC with lower D14C under less coastal rainfall during La Niña could further elevate the D14CTOC. Lower scanning XRF (K+Ti)/2 (indicating lower terrigenous input), higher scanning XRF Sr/Ti as well as acid-leachable elements (reflecting higher biogenic components), and higher D14CTOC occur during La Niña. During the El Niño period, the phenomena are opposite. Spectrum analyses of the Southern Oscillation Index (SOI) and the D14CTOC as well as the comparison of SOI and SBB-8-2012 records support our scenarios.